Respiratory Diseases in Poultry: Clinical and Pathological Aspects and Their Occurrence in Indonesia - ., Tarmudji (Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
Some of respiratory diseases in poultry are caused by virus, bacteria, mycoplasma, fungi or combination of various agents. Respiratory diseases in commercial poultry farms (broiler or layer) that are commonly found in Indonesia are : Avian Influenza (AI-H5NI), Newcastle Disease (ND), Infectious Bronchitis (IB), Infectious Laryngotracheitis (ILT), Swollen Head Syndrome (SHS), Chronic Respiratory Disease (CRD), Infectious Coryza, Fowl cholera, Colliseptichemia and Aspergillosis. Spore of Aspergillus sp . and ND/IB viruses (in live vaccine) occasionally exhibited respiratory disorder in chickens (0-2 weeks). Other respiratory diseases can occur in chickens after two weeks of age and are caused by various infectious agents (mixed infection). Two or more infection agents resulted in more severe respiratory disease (in clinical signs and pathological lesions) than a single infection agent. Some of respiratory diseases have similar clinical signs (nasal discharge, lacrimation, coughing and gasping). However, by more thoroughly observation on the outbreak occurrence, causal agents, age of chickens, characteristics of epidemiology and clinical signs. the diagnose of the disease could be defined. Pathological diagnostic approach is commonly used in animal health management of commercial poultry farms. Pathognomonic lesions of organs caused by the diseases could give an accurate diagnose. High Pathogenic Avian Influenza (AI/HPAI) is the most important of the poultry diseases in Indonesia, since it is very contagious to other birds and human resulted in a negative impact on the National Poultry industry and human health (zoonosis) . Key words: Respiratory disease, chicken, clinical signs, pathology, Indonesia